Health education for housewife ini utilizing household waste - Ika Kustiyah Oktaviyanti; Lisda Hayatie; Joharman Joharman; Hendra Wana Nur'amin; Wahyuni Wahyuni; Nur Annisa Humaira; Auryn Widyananda Sindunata; Agatha Theodora Desvita Raharjo; Nasywa Melanie Sugiyanto; Hana Najma Maulidya (Community Empowerment, 2023)
The volume of waste originating from households is increasing day by day, this condition will cause new problems such as disease outbreaks and a decrease in environmental quality. The purpose of this community service is to improve and empower housewives in managing organic waste originating from household organic waste. The method of this program is health education with material explanations, demonstrations, and discussions. As a result, participants know the steps to make compost/fertilizer from household waste and are able to produce it properly.